Antropo-Sociological Study on Jewish Emigrants to Palestine - Sikora, Paweł (Anthropological Review, 1987)
The material was collected in 1936 by dr Gizela Każdanówna and referred to candidates for emigration to Palestine. The studies were carried out in the preparatory groups in the following places: Cracow, Tarnow, Krzeszowice and Bielsko-Biala. The material comprised 235 men in the age from 17 to 30 years (mean: 22 years and 9 months). The number of investigated women was 215 in the age from 19 to 29 years (mean: 22 years and 4 months).The investigated subjects originated mainly from workers, craftsmen and small shopkeepers. Anthropological examinations covered descriptive features (colour of eyes and hair, nose profile), and the measurement features comprised: stature, head measurements (length and breadth), face measurements (total face height, upper face height, nose height, face breadth, nose breadth). In women there was also an anamnesis concerning the appearance of the menarche. Hie above material was statistically elaborated, the obtained results were compared with results referring to Jewish academic youth of Lvov University in 1927. There are higher differences in the stature, which can be the results of a different social composition of the academic youth. Insignificant differences occur also in the breadth of face and in the hight of the upper face.